Al excess extends Hall‐Petch relation in nanocrystalline zinc aluminate - Sotelo Martin, Luis E.; Castro, Ricardo H. R. (Journal of the American Ceramic Society, 2022)
The increase in hardness with decreasing grain size is a well‐established size effect known as the Hall‐Petch relationship. In ceramics, there has been controversy surrounding the existence of a low size limit below which size‐induced hardening no longer occurs and softening is observed instead. Here, this so‐called inverse Hall‐Petch relationship was observed in quasi‐stoichiometric dense nanocrystalline zinc aluminate while an extension of the normal Hall‐Petch behavior was demonstrated by Al‐rich zinc aluminate nanoceramics. Vickers hardness increased with grain refinement for quasi‐stoichiometric samples prepared by High Pressure Spark Plasma Sintering, exhibiting a maximum of 18.6 GPa at a grain size of 21.4 nm. Conversely, Al‐rich zinc aluminate produced by the same technique strengthened up to 19.2 GPa at 12.6 nm grain sizes. Cross‐sections of Vickers indentation imprints showed that while quasi‐stoichiometric zinc aluminate showed a change in sub‐surface cracking pattern from larger to smaller grain sizes (before and after the inverse Hall‐Petch), the Al‐rich samples had sub‐surface cracking similar to those found in large grain sizes in quasi‐stoichiometric samples. These results suggest that softening at small grain sizes is driven by the activation of shear and fracture at weak grain boundaries which can be mitigated by Al enrichment.